Cirebon Law Enforcement is Using the Michat App to Combat Online Prostitution - Legi Vanesa, Diva (Jurnal Legisci, 2023)
The purpose of this study is to (1) evaluate the efforts made by law enforcement to combat online prostitution offences in Cirebon via the MiChat app. (2) Being aware of the challenges faced by law enforcement officers in Cirebon when handling online prostitution offences via the MiChat program. Cyber Prostitution is a form of prostitution that takes place online. It is illegal and is governed by Law No. 11/2008 (ITE Law), which lists it as a criminal act in Article 27. Online prostitution through the MiChat app is one of the many offenses that violate moral standards that are currently on the rise. The quantity of prostitutes still engaged in online prostitution using the MiChat software serves as evidence of this. The Regional Regulation's criminal penalties do not have a deterrent impact, Satpol PP's human resources are of poor quality, there are no official vehicles available for transportation during operations or raids, and social media abusers are among the problems impeding progress. The younger generation appears to be blind to the Cirebon culture's diversity and the influence of social media technologies, which can have a detrimental effect.